2000
DOI: 10.2151/jmsj1965.78.4_357
|View full text |Cite
|
Sign up to set email alerts
|

Ensemble Hindcast Experiments for the Flood Period over China in 1998 by Use of the CCSR/NIES Atmospheric General Circulation Model

Abstract: Sets of numerical hindcast experiments were carried out to study the excessive rain that happened over

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(13 citation statements)
references
References 17 publications
0
12
0
1
Order By: Relevance
“…In addition, the sea surface temperature (SST) anomalies over the tropical and northern midlatitude oceans are also documented having close linkages with the EASM. For example, Wang et al (2000a) and Wang et al (2000b) demonstrated the impact of the tropical eastern Pacific SST on the EASM. Huang and Li (1988) as well as Li and Mu (2001) addressed that the tropical western Pacific and Indian Ocean play important roles in the variability of the EASM.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the sea surface temperature (SST) anomalies over the tropical and northern midlatitude oceans are also documented having close linkages with the EASM. For example, Wang et al (2000a) and Wang et al (2000b) demonstrated the impact of the tropical eastern Pacific SST on the EASM. Huang and Li (1988) as well as Li and Mu (2001) addressed that the tropical western Pacific and Indian Ocean play important roles in the variability of the EASM.…”
Section: Introductionmentioning
confidence: 99%
“…The T42L20 version, which has medium resolution, was used. This model contains comprehensive physical processes, and has a reasonably high degree of accuracy for modeling mean climate [11] . The model was integrated for 20 years in the climatological run, in which SST and sea ice data is that of the AMIP (Atmospheric Model Intercomparison Project) climatological monthly data.…”
Section: The Model and Numerical Experimental Designmentioning
confidence: 99%
“…Since the model climatology has been described elsewhere [11] , only the sea-level pressure prediction for the mean climate as presented in Fig.1 is shown. The model reasonably simulates the distribution and strength of the pressure systems, including the low pressure over Eurasia and the sub-tropical high-pressure system.…”
Section: Precipitationmentioning
confidence: 99%
“…At the same time, many scientists [10][11][12][13][14][15] show that initial conditions are also very important to short-term climate prediction, especially in East Asia, initial conditions cannot be neglected if one aims for forecasting short-term climatic anomalies because of internal atmospheric chaos. So accurate initial conditions are necessary.…”
Section: Introductionmentioning
confidence: 99%